MEDIA MASSA BERBAHASA BALI SEBAGAI MEDIA PEMERTAHANAN BAHASA BALI DI PROVINSI BALI: MEDIA MASSA BERBAHASA BALI SEBAGAI MEDIA PEMERTAHANAN BAHASA BALI DI PROVINSI BALI - I Kadek Widiantana (UHN IGB Sugriwa Denpasar, 2022)
Balinese language as the mother tongue of the Balinese people is inherited and used until now. As part of the cultural treasures, the existence of the Balinese language is very important to be preserved. The Provincial Government of Bali, as the highest policy holder in the region, has also issued various legal regulations, both in the form of regional regulations and governor regulations in preserving the Balinese language. Policies from the local government certainly require support from all components of Balinese society as supporters and users of the Balinese language. In addition to the efforts carried out by the local government, the mass media in Bali have also long played a role in preserving the Balinese language, one of which is by including Balinese language rubrics in the mass media published, either in daily, weekly or monthly editions. However, the contribution of the Balinese-language mass media is felt to have received less attention from the public, including the government, so that its existence is fluctuating. Therefore, it is important to conduct a study on how the development, existence and also the supporting or inhibiting factors of maintaining the Balinese language through the Balinese language mass media. When viewed from its development, the mass media in Balinese language has been developing for a long time. The Balinese language mass media is still effective in conveying information to the public, because most Balinese people are still active in using the Balinese language. Factors supporting the existence of Balinese-language mass media in Bali include, among others, the support of the Bali provincial government in preserving the Balinese language and literature in the form of regulations in the form of governorates and local regulations; the idealism of the owners or managers of Balinese-language mass media in Bali; the development of Balinese language communities; there are universities that open Balinese language departments. The inhibiting factors for the existence of Balinese-language mass media in Bali include very little interest in writing by the Balinese; the Balinese language is only a spoken language, not a written language; the world of literature is very minimal; operating costs